The Effect of Capital Factors on Resilience and Sustainability of the Homestay Business in Facing the Covid-19 Pandemic - I Made Adi Suwandana; I Made Sumada; Nyoman Diah Utari Dewi; Putu Eka Trisna Dewi; Anak Agung Putu Gede Bagus Ari Susandya (International Journal of Social Science and Business, 2022)
The Covid-19 pandemic has placed great attention on leaders in business and other sectors. The scale and uncertainty it faces can be tricky. The resilience of homestays in the face of the Covid-19 pandemic cannot be separated from the forming factor, namely the approach to capital factors. The purpose of this study is that resilience analysis plays a role in mediating the influence of human capital, economic capital, and physical capital on the sustainability of the homestay business in the face of the Covid-19 pandemic in the implementation of the Covid-19 green zone in the Sanur Region. This research type uses quantitative methods to design research variables and formulate hypotheses. This research was conducted on 63 homestay units implementing the Covid green zone in Sanur City, Denpasar City. The research sample was determined purposively as many as 124 homestay business actors. Data was collected using a questionnaire. Data analysis using path analysis. The analysis results show that human capital, economic capital, social capital, and physical capital have a positive and significant effect on homestay resilience and the sustainability of the homestay business. Homestay resilience plays a role in mediating the influence of human capital, economic capital, and physical capital on the sustainability of the homestay business but does not mediate social influences.